Developing the System of Values based on Cultural Quotient of University Presidents - Afsaneh Fazeli; Mahmood Ekrami (Allameh Tabataba'i University Press, 2014)
This study has been carried out for the purpose of investigating the relation between the value system and cultural quotient of the presidents of Allameh Tabataba'i University. The statistical population comprises all presidents serving with the university, coming to 70 subjects, out of whom 56 responded to the questionnaires and their emerging data were analyzed. In order to measure the value system variables, questionnaire developed Allport - Vernon - Lindzey and in order to measure cultural quotient as a general concept and its variables, the Cultural Quotient Questionnaire (CQS) was used. Research findings suggest that the levels of variables of political value, theoretical value, and economic value are high in the value system, and the level of variable of artistic value is medium, and levels of variables of social value and religious value are low. The levels of variables of metacognition and motivation are high, and those of cultural quotient as a general concept and behavior are medium, and the level of the variable of cognition is low. Ranking of the value system among the presidents is as follows: 1. Political value, 2. scientific value, 3. economic value, 4. Artistic value, 5. social value, 6. religious value; and ranking of cultural quotient as a general concept and its variables is as follows: 1. metacognition, 2. Motivation, 3. Behavior, and 4. Cognition.